Evolution of the structural and optical properties of silver oxide films with different stoichiometries deposited by direct-current magnetron reactive sputtering - 赵孟珂 梁艳 郜小勇 陈超 陈先梅 赵显伟 赵建伟 刘凤娟 黄海琴 胡佐富 张希清 (Chinese physics B, 2012)
Nitrogen doping of silver oxide （AgxO） film is necessary for its application in transparent conductive film and diodes because intrinsic AgxO film is a p-type semiconductor with poor conductivity. In this work, a series of AgxO films is deposited on glass substrates by direct-current magnetron reactive sputtering at different flow ratios （FRs） of nitrogen to 02. Evolutions of the structure, the refiectivity, and the transmissivity of the film are studied by X-ray diffractometry and sphectrophotometry, respectively. The specular transmissivity and the specular refiectivity of the film decreasing with FR increasing can be attributed to the evolution of the phase structure of the film. The nitrogen does not play the role of an acceptor dopant in the film deposition.